(untitled) - Waltner-Toews, David (Cambridge, UK, 2004)
Improving the health of people and animals, and improving the health, integrity or sustainability of ecosystems are laudable and important objectives. Can we do both? There are no ecosystems untouched by human activity, and there are worrying signs that the world's ecosystems are reaching the limits of their ability to adapt to human impacts. Drawing on fields as diverse as epidemiology and participatory action research, philosophy and environmental sciences, ecology and systems sciences, this book is about searching for solutions to complex problems to produce a new science for sustainability.
Keywords: Ecosystem management,Environmental health,Hệ thống sinh thái